Psychoneurobiology Research and Personalized Treatment of Schizophrenia - Sumiyoshi, Tomiki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Schizophrenia is a common disease characterized by psychotic symptoms (e.g., delusion, hallucinations, blunted affect) and disturbances of cognitive function (e.g., memory, abstraction, attention). If not treated properly, patients may experience serious consequences in terms of social function. Much endeavor in several disciplines of medical science has been made to overcome the paucity of effective treatments for unmet needs, including cognitive impairment associated with schizophrenia.This Book, contributed by experts from various regions of the globe, provides up-to-date information to facilitate the development of personal therapeutics for this enigmatic illness.